Analysis of HPV Vaccination Willingness amongst HIV-Negative Men Who Have Sex with Men in China - Wei He; Haiying Pan; Bing Lin; Xiaoni Zhong (Vaccines, 2021)
Objective: Men who have sex with men (MSM) are high-risk groups of human papillomavirus (HPV) infection, the best measure to prevent this is the HPV vaccine. However, few studies have investigated HPV vaccination willingness in the MSM population in China. We aimed to explore the willingness of human immunodeficiency virus (HIV)-negative MSM for HPV vaccination and the factors affecting their willingness to vaccinate. Methods: We adopted a non-probability sampling method to recruit HIV-negative MSM volunteers. Participants completed a questionnaire, including sociodemographic characteristics, sexual behavior characteristics, HPV infection and vaccine-related knowledge, risk perception, and HPV vaccination willingness and promotion attitudes. Results: Of the 406 HIV-negative MSM surveyed, 86.21% were willing to receive HPV vaccine. HPV infection and vaccine-related knowledge (odds ratio [OR] = 2.167, 95% confidence interval [CI] = 1.049–4.474), HPV infection risk perception (OR = 5.905, 95% CI = 1.312–26.580), and HPV vaccine promotion attitude (OR = 6.784, 95% CI = 3.164–14.546) were all related to HPV vaccination willingness. Conclusion: MSM have a high willingness for HPV vaccination. Strengthening health education for MSM, raising their awareness of HPV infection and vaccines, and promoting their risk perception of HPV infection will help increase their willingness for HPV vaccination.